A cross‐sectional analysis of Yelp and Google reviews of hospitals in the United States - Tony Zitek; Joseph Bui; Christopher Day; Sara Ecoff; Brijesh Patel (Journal of the American College of Emergency Physicians Open)
Abstract Objective Patient satisfaction is now an important metric in emergency medicine, but the means by which satisfaction is assessed is evolving. We sought to examine hospital ratings on Google and Yelp as compared to those on Medicare's Care Compare (CC) and to determine if certain hospital characteristics are associated with crowdsourced ratings. Methods We performed a cross‐sectional analysis of hospital ratings on Google and Yelp as compared to those on CC using data collected between July 8 and August 2, 2021. For each hospital, we recorded the CC ratings, Yelp ratings, Google ratings, and each hospital's characteristics. Using multivariable linear regression, we assessed for associations between hospital characteristics and crowdsourced ratings. We calculated Spearman's correlation coefficients for CC ratings versus crowdsourced ratings. Results Among 3000 analyzed hospitals, the median hospital ratings on Yelp and Google were 2.5 stars (interquartile ratio [IQR], 2–3) and 3 stars (IQR, 2.7–3.5), respectively. The median number of Yelp and Google reviews per hospital was 13 and 150, respectively. The correlation coefficients for Yelp and Google ratings with CC's overall star ratings were 0.19 and 0.20, respectively. For Yelp and Google ratings with CC's patient survey ratings, correlation coefficients were 0.26 and 0.22, respectively. On multivariable analysis, critical access hospitals had 0.22 (95% confidence interval [CI], 0.14–0.30) more Google stars and hospitals in the West had 0.12 (95% CI, 0.05–0.18) more Google stars than references standard hospitals. Conclusion Patients use Google more frequently than Yelp to review hospitals. Median UnS hospital ratings on Yelp and Google are 2.5 and 3 stars, respectively. Crowdsourced reviews weakly correlate with CC ratings. Critical access hospitals and hospitals in the West have higher crowdsourced ratings.